Autentikasi Bunga R.tomentosa dari Resiko Adulterasi M. Candidum dengan Metode Spektrofotometri UV-VIS Kombinasi Khemmometrik: Authentication of R.tomentosa Flowers From the Risk of M. Candidum Adulteration Using Chemometric Combination UV-VIS Spectrophotometry Method - Samsul Hadi; Kunti Nastiti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
R. tomentosa flowers have various activities and these activities are different from M. candidum flowers, but have similar flowers so the risk of mixing is very high. Therefore, this study aims to prevent the occurrence of mixtures using UV-VIS spectrophotometry method combined with chemometrics. The method used in this study was the extracts of the two species were dissolved with methanol p.a and scanned the spectra at a wavelength of 200-400 nm, data analysis using partial least squares. The results obtained in the authentication of Bunga R.tomentosa produced various models, at 248.14-222.5 nm scanning resulted in data RMSEC: 2.61, R2: 0.9971, RMSEP:5.78, R2: 0.9951 and RMSECV:9.19, R2: 0.9655, On scanning 298.43- 56.36nm produces data RMSEC:0.929, R2: 0.9996, RMSEP:3.54, R2: 0.9956 and RMSECV:10.5,R2:0.9591, by looking at the two data, the lowest RMSE value and the highest R2 value are selected. The conclusion in this study is that the best model for R.tomentosa authentication is the second derivatization with a wavelength of 298.43-256.36nm.